2000
DOI: 10.1034/j.1600-0447.2000.101006433.x
|View full text |Cite
|
Sign up to set email alerts
|

Finnish adoptive family study: sample selection and adoptee DSM‐III‐R diagnoses

Abstract: The genetic liability to 'typical' DSM-III-R schizophrenia is decisively confirmed. Additionally, the liability also extends to a broad spectrum of other psychotic and non-psychotic disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
87
0
2

Year Published

2001
2001
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(94 citation statements)
references
References 10 publications
(17 reference statements)
5
87
0
2
Order By: Relevance
“…The original studies of Kety et al (1968; found evidence for spectrum disorders genetically related to schizophrenia in the adopted away offspring of schizophrenic mothers. The Finish Adoptive Family Study of schizophrenia (Tienari et al, 2000) reported a life time prevalence of schizophrenia of 6.7% in the adopted offspring of schizophrenic mothers compared to 2% in controls but more strikingly 17% of adoptees with a schizophrenic mother and 4% of control adoptees attracted a diagnosis of either schizophrenia or a broadly defined schizophrenia spectrum disorder. Spectrum disorders included schizoaffective disorder, delusional disorder, bipolar disorder, psychotic depression and the personality disorders categorised as schizotypal, paranoid and schizoid.…”
Section: Clinical Spectra Of Schizophrenia and Bipolar Disordermentioning
confidence: 96%
“…The original studies of Kety et al (1968; found evidence for spectrum disorders genetically related to schizophrenia in the adopted away offspring of schizophrenic mothers. The Finish Adoptive Family Study of schizophrenia (Tienari et al, 2000) reported a life time prevalence of schizophrenia of 6.7% in the adopted offspring of schizophrenic mothers compared to 2% in controls but more strikingly 17% of adoptees with a schizophrenic mother and 4% of control adoptees attracted a diagnosis of either schizophrenia or a broadly defined schizophrenia spectrum disorder. Spectrum disorders included schizoaffective disorder, delusional disorder, bipolar disorder, psychotic depression and the personality disorders categorised as schizotypal, paranoid and schizoid.…”
Section: Clinical Spectra Of Schizophrenia and Bipolar Disordermentioning
confidence: 96%
“…Tienari et al (27) has recently demonstrated interactions between genetic and environmental factors in schizophrenia. We could not investigate both genetic and environmental factors because data on familiality are not available for the cohort.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 However, the limits of this spectrum and its relationship to other psychoses, affective and nonaffective, and nonpsychotic affective disorders remain uncertain. [14][15][16] Finally, although it is clear that individual differences in liability to schizophrenia are substantially genetic, we have no clear idea what form this 'liability' actually takes. That is to say, we are not yet able to identify the endophenotypes that are intermediate between genetic predisposition and the clinical phenotype of schizophrenia.…”
Section: Defining the Phenotypementioning
confidence: 99%